2023
DOI: 10.3390/biomimetics8040347
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing an Oxidized Biopolymer to Enhance the Bonding of Glass Ionomer Luting Cement Particles for Improved Physical and Mechanical Properties

Abstract: This study aimed to determine the reinforcing effect of two weight ratios of Gum Arabic (GA) natural biopolymer, i.e., 0.5% and 1.0% in the powdered composition of glass ionomer luting cement. GA powder was oxidized and GA-reinforced GIC in 0.5 and 1.0 wt.% formulations were prepared in rectangular bars using two commercially available GIC luting materials (Medicem and Ketac Cem Radiopaque). The control groups of both materials were prepared as such. The effect of reinforcement was evaluated in terms of microh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The GF at 0.5 wt.% might promote a more uniform distribution of particles and reduce the presence of voids or defects, leading to a more consistent and harder material. Decreased properties of 1.0 wt.% GF-GIC composites in both formulations might be attributed to a combination of factors related to fibre dispersion, interfacial bonding, matrix disruption, mechanical mismatch, and specimen variability [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GF at 0.5 wt.% might promote a more uniform distribution of particles and reduce the presence of voids or defects, leading to a more consistent and harder material. Decreased properties of 1.0 wt.% GF-GIC composites in both formulations might be attributed to a combination of factors related to fibre dispersion, interfacial bonding, matrix disruption, mechanical mismatch, and specimen variability [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Some GIC formulations might already contain additives or components that interact favourably with GF, leading to enhanced mechanical properties. On the other hand, certain compositions might have chemical interactions that interfere with the reinforcing effect of the fibres, resulting in decreased mechanical properties [3,23]. The chemical interactions at the interface between the fibres and the GIC matrix contributed to the improved mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the addition of GA did not significantly affect the film thickness or water contact angle of the GIC formulations, indicating that modifications enhanced mechanical properties without compromising handling characteristics [17][18][19]. This outcome implies that GA reinforcement significantly increases the performance and durability of the GICs and, therefore, will find utility in a wide range of applications in dentistry [16].…”
mentioning
confidence: 92%
“…Alsunbul et al [16] explored the reinforcing effects of gum Arabic (GA) on glass ionomer cements (GICs). In this experiential work, it was demonstrated that the addition of 0.5 wt.% GA into the GIC remarkably increased the flexural strength, fracture toughness, and tensile strength, but reduced the internal porosity.…”
mentioning
confidence: 99%
“…A recently published study showed that the binding affinity between GA and glass ionomer cement (GIC) is improved, thus enhancing the mechanical properties such as flexural strength, fracture toughness and tensile strength of the set GIC. 13 In another study, GA powder was successfully reinforced into GIC for enhanced hardness, diametral tensile strength and compressive strength. 14 …”
Section: Introductionmentioning
confidence: 99%